Safety profile of tirzepatide: A real-world pharmacovigilance analysis of EudraVigilance database - Atul Khurana; Syed Arman Rabbani; Mohamed El-Tanani; Mandeep Kumar Arora; Shrestha Sharma; Harikesh Dubey; Alaa A. Aljabali; Murtaza M. Tambuwala (Clinical Epidemiology and Global Health)
Background: Tirzepatide has demonstrated superior efficacy in glycemic control and weight reduction compared to existing GLP-1 receptor agonists. However, its safety profile remains to be fully elucidated in real-world settings. This study examines its safety profile using the EudraVigilance database. Methods: We conducted a pharmacovigilance analysis of individual case safety reports (ICSRs) with tirzepatide as the suspected drug using EudraVigilance database. A descriptive analysis was carried out to explore the characteristics of these ICSRs. Disproportionality analysis was performed using reporting odds ratio (ROR) and proportional reporting ratio (PRR) metrics. Results: We evaluated 2102 ICSRs where tirzepatide was implicated as the suspected drug. Majority of the ICSRs were reported by healthcare professionals (1299, 61.8 %). A total of 5774 AEs associated with tirzepatide were reported with majority being classified as serious (4914, 85.1 %). The outcome for most AEs (47.7 %, 2754 AEs) was reported as unknown, whereas 30.9 % (1784 AEs) were reported as recovered/resolved. AEs associated with the ‘Gastrointestinal Disorders’ SOC (1873, 32.4 %) were the most frequently reported, followed by those related to ‘Injury, poisoning and procedural complications’ SOC (641 AEs). Pancreatitis (363) and vomiting (274) emerged as the most commonly reported AEs. The disproportionality analysis indicated a higher reporting frequency of gastrointestinal AEs for tirzepatide (ROR: 1.35, 95 % CI: 1.47-1.23; PRR: 1.16, 95 % CI: 1.26-1.06) compared to semaglutide, dulaglutide, liraglutide and exenatide. Conclusion: This study underscores tirzepatide's safety profile in real-world settings. It highlights the need for ongoing monitoring, especially considering tirzepatide's recent introduction to the market.